View from Front Porch of the Trinidad Country Club: Giant Saman [sic] Tree in Foreground - (:unkn) unknown (Queen's Park Hotel Co. Ltd., Trinidad, 2009)
A picture of a giant Samaan Tree surrounded by well manicured lawn of the Trinidad Country Club located in Maraval. Postcard no. 2.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Clubs--Trinidad and Tobago; Trees--Trinidad and Tobago